Urgensi Knowledge Management Dalam Pengembangan Profesionalisme Guru - Mila Alvionita; Dea Wanda Milarahma Putri (Program Studi Manajemen Pendidikan Islam, 2024)
This article aims to gain an in-depth understanding of the Urgency of Knowledge Management in Teacher Professionalism Development. School policies that change frequently make education staff, policy makers and teachers need relevant knowledge to do their jobs. Knowledge Management can be a solution for educators to manage change as it has been considered a possible strategy to address problems in the business sector. This study uses a type of descriptive qualitative research based on library research where the researcher uses various literature to obtain research data and uses content analysis. Based on the results of the research, Education functions as one of the sources of knowledge, so Knowledge Management has a very important role in it. Knowledge development must be supported by information technology to facilitate access and improve the quality of knowledge sharing as well as knowledge management, which will result in improved quality and competitiveness. Professional teachers are teachers who have the necessary skills and competencies to carry out educational and teaching duties. Teacher performance is very important for the success of education because the performance of teachers in carrying out their duties greatly affects the quality of education. Thus, professional teachers can and have the ability to carry out their roles and responsibilities as educators in the field concerned.